When Shadow Removals Collide: Searching for Solutions to the Legal Black Holes Created by Expedited Removal and Reinstatement - Jennifer Lee Koh (Washington University Law Review, 2018)
Immigration scholarship has begun to explore the prominence of shadow removals—deportations that are executed by front-line agency officials acting outside the presence of an immigration judge—which now constitute the majority of all reported removals. This Article explores two of the most common forms of shadow removals, expedited removal and reinstatement of removal, and the collision of the two. Expedited removal has typically been perceived as a border enforcement tool, used against persons with limited ties to the United States. Reinstatement of removal exists for persons who enter the U.S. without authorization following a prior removal. The rising use of each streamlined procedure is, on its own, troubling from a fairness, accuracy, and rule of law perspective. But like chemical compounds mixing and creating new substances, expedited removal and reinstatement interact to produce unique situations in which the law renders people forever subject to immediate deportation based primarily on the existence of a brief encounter at some point in the past with a border official. These situations are akin to legal black holes in immigration law, and have not been examined in any of the scholarly literature to date. This Article is the first to consider the interplay of expedited removal and reinstatement. It traces the operation of the two removal processes, both independently and in combination with each other. It emphasizes the harsh statutory bars on judicial and habeas review, and the resulting inability of the federal judiciary to ameliorate the harshness of removal in this context. The Article then suggests that the use of reinstatement based on prior expedited removal orders fails the basic administrative law requirement that federal agencies demonstrate reasoned decision-making and avoid arbitrary or capricious action. Relying on the Supreme Court’s decision in Judulang v. Holder, which applied arbitrary and capricious review in the deportation context, the Article encourages courts to more closely scrutinize the use of reinstatement based on expedited removal.
Keywords: immigration law; deportation; immigration judge; shadow removal; expedited removal; reinstatement of removal; prior removal; Judulang v. Holder; arbitrary and capricious review; Habeas Review; constitutional avoidance; expedited removal exception; procedural due process